2022
DOI: 10.1021/acs.chemmater.2c00533
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High-Efficiency Organic Photovoltaics from a New Completely Amorphous Donor Polymer

Abstract: The development of non-fullerene acceptors (NFAs) such as ITIC and Y6 has greatly improved the efficiency of polymer solar cells. Therefore, focus should now shift towards the design of donor polymers with better compatibility with these NFAs to attempt to push efficiencies to higher levels. The indacenodithienothiophene (IDT) unit has up till now been typically incorporated into donor polymers for fullerene-based solar cells; however, the application of IDT-based polymers in NFA solar cells is rare. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
2
12
1
Order By: Relevance
“…Tensile elastic modulus at room temperature vs the T g of p­(g 4 2T-T) from ref (blue open circle), of conjugated polymers with alkyl side chains from refs (blue filled symbols) and refs , [blue half-filled symbols; tensile elastic modulus estimated using E = 2 G (1 + υ ), where G is the shear elastic modulus and assuming a Poisson ratio of υ = 0.5] as well as the value measured in this study for p­(g42T-T) (pink open diamond), which increases by at least two orders of magnitude (red arrow) upon the addition of 11 or 20 vol % CNF (pink filled diamonds).…”
Section: Introductionsupporting
confidence: 72%
“…Tensile elastic modulus at room temperature vs the T g of p­(g 4 2T-T) from ref (blue open circle), of conjugated polymers with alkyl side chains from refs (blue filled symbols) and refs , [blue half-filled symbols; tensile elastic modulus estimated using E = 2 G (1 + υ ), where G is the shear elastic modulus and assuming a Poisson ratio of υ = 0.5] as well as the value measured in this study for p­(g42T-T) (pink open diamond), which increases by at least two orders of magnitude (red arrow) upon the addition of 11 or 20 vol % CNF (pink filled diamonds).…”
Section: Introductionsupporting
confidence: 72%
“…Previous studies of the Y6 system have shown it is ambipolar, with the mobility of electrons reported to be a factor of 2-3 times greater than that of holes in intrinsic Y6-only devices. [22,56] Both the Y6 hole mobility reported in these studies and the PIDT-T8BT hole mobility reported in our previous work are lower than the maximum carrier mobility determined in this work, [24] leading us to assign the mobility measured by photoCE-LIV to electron transport in Y6. To rationalize why this mobility increased by more than an order of magnitude as the D:A ratio was increased from the 1:50 to the 1:1, we consider both the complex nature of charge generation and recombination revealed by the TA measurements in this work and the data and interpretations reported in previous studies of low donor-content devices with Y6 as an electron acceptor.…”
Section: Transient Electrical Measurements Of Carrier Dynamics In Ope...contrasting
confidence: 52%
“…However, the PIDT-T8BT:Y6 solar cells using the conventional donor:acceptor (D:A) ratio of 1:1.2 only offered modest photovoltaic performance, which discouraged the continued study of this polymer. [24] Inspired by the studies on low donor blends paired with Y6, [22][23] a series of OPVs containing PIDT-T8BT:Y6 over a broad range of D:A ratios were fabricated and investigated for this study. In this work, PIDT-T8BT:Y6 OPVs with a D:A ratio of 1:10 achieved over 10% PCE.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In the past decade, with the advent of more complex monomer structures, researchers found that, instead of long-range ordering (i.e., crystalline packing), the local segmental order (e.g., co-facially stacked planar backbone segments with tie polymer chains) can enable efficient long-range charge transport in a near amorphous state. [11][12][13] This unique charge transport mechanism might result from the high coplanarity of rigid backbone with long conjugation length, which in turn allows CPs to have more design space for coupling new functions, such as mechanical softness and stretchability, while maintaining electronic performance. 14 It is immediately evident that the segmental order strongly depends on the chain rearrangement, especially the crystallization process, during deposition and post-thermal treatment.…”
Section: Introductionmentioning
confidence: 99%